Formative assessment of learning: the class council experience - Magnata, Rúbia Cavalcante Vicente (2015)
This study aimed to evaluate the class council as a tool for the formative assessment of learning. Its intent was to identify the concepts of learning assessment that pervade the experience of class councils in the Colégio de Aplicação of the Federal University of Pernambuco. Formative assessment promotes the development of students, as it is built in a continuous and permanent process for monitoring learning. Observations of class council meetings, semi-structured interviews and document analysis were carried out based on case study methodology. The results show that the conceptions which are intrinsic to the dynamic functioning of class councils point to the understanding and practice from the perspective of formative assessment, and that the practices of class council development indicate the possibility of implementing a constructive and collective form of assessment.